Penegakan Hukum terhadap Tindak Pidana Pemerasan Menggunkan Teknologi Media Sosial di Polresta Yogyakarta - Nurmiati Nurmiati; Harti Winarni (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This research was conducted due to the rapid development of technology and social media, which have a significant impact, including the increase in cybercrime. Technology is now often misused to commit legal violations, such as extortion through social media. This research employs a Normative Juridical and Empirical approach. The normative approach is conducted by examining regulations and literature, while the empirical approach is through direct interviews with sources. Data is collected through literature studies and interviews. The results show that extortion on social media at the Yogyakarta Police is caused by economic factors and the perpetrators' confidence in technology. Law enforcement is carried out through the stages of reporting, investigation, arrest, inquiry, and the preparation of case files.